The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1st International Conference on Social and Political Development (ICOSOP 2016) 2017
DOI: 10.2991/icosop-16.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

Gen C and Gen Y: Experience, Net emotional Value and Net Promoter Score

Abstract: Abstract-We live in a world with more brands and more choice than ever before. This Study examines Generation C and Y, how they feel, sense and interact with brands. Memorable experience will affect to positive emotion and brand loyalty The data for study represent 200 participant Gen C and Gen Y accros 145 brands including local, national and multinational brand. Customer experience measured against customer expectation across all moment contanct with brand. Net Emotional Value (NEV) measured by single number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
0
10
2
3
Order By: Relevance
“…E-CRM is another critical factor, which most millennials liked. Customer experience is the way to winning the stiff competition and acting as the estimation of separation from different brands [117]. All three aspects of E-CRM, identify, acquire, and retain, were successfully used by the insurers operating digital platforms [53,54].…”
Section: Discussion Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…E-CRM is another critical factor, which most millennials liked. Customer experience is the way to winning the stiff competition and acting as the estimation of separation from different brands [117]. All three aspects of E-CRM, identify, acquire, and retain, were successfully used by the insurers operating digital platforms [53,54].…”
Section: Discussion Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…The NPS was found to vary based on the age of the respondent. Market research (Medallia, 2016) and academic (Kasch, 2016; Situmorang, 2017) projects have found that Millennials tend to provide a lower score compared with Non-Millennials. Eskildsen and Kristensen (2011) found that gender also influenced how customers responded to the NPS question.…”
Section: Challenges With the Npsmentioning
confidence: 99%
“…Location-based social media are used by tourists because of the need for information and connectivity – for instance, looking up maps, places to eat, tourism recommendations and shopping centres on the go, in addition to games, social media sites and apps for entertainment or to share experiences and recommendations (word-of-mouth) with others while within the tourism context (Tussyadiah, 2012; Romero, 2018). Recommendations are frequently shared by consumers in the moment, through location-based marketing (Situmorang et al , 2017), therefore, can be beneficial for service customer experience, but greater understanding relating to impact on the customer experience is necessary. Social media has been concluded to have a positive relationship with engagement, increasing social capital, civic engagement and political participation, although there is also evidence of negative use of the internet for recreational purposes (Skoric et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%